ESTIMATION OF YIELD AND ADAPTIVE CHARACTERISTICS OF BUCKWHEAT GENEPOOL - Tryhub, O. V.; Kutsenko, O. M.; Liashenko, V. V.; Dudka, K. O. (Scientific Progress & Innovations, 2021)
Solving the problem of ensuring the breeding process by selection material of various origin and genetic basis was substantiated and disclosed in the article. This is one of the essential conditions for effective crea-tion of varieties and hybrids with corresponding parameters of yield characteristics and indicators of their stable manifestation in changeable and often contrast environmental conditions. The study of different selection material, its assessment, description and differentiation according to definite levels of signs’ manifestation is possible while working with the collection samples of the National Collection of Buckwheat in Ukraine. The use of optimal approaches to applying the techniques of assessing the impact of environmen-tal factors and genetic potential of the variety material is not less important. Complex using of assessment techniques enables to optimize considerably the process of searching parent forms. The researches as to the article theme were conducted for 20 years. To analyze the obtained data of studying yield characteristics, the methods of estimating the resistance to the action of abiotic factors and determining the linear regression coefficient (bi), dispersion coefficient (S2i), variety resistance to stress and genetic plasticity, stability index, homeostatic balance and breeding value were used. As a result of studying the set of samples amounting more than 200, the collection was formed (39 samples), based on which the effectiveness of applying different techniques on buckwheat was analyzed and drawbacks of certain methods were revealed as well as the best ones were recommended. As the result of assessment, the following best varieties by stability parameters among the set of geographically remote cultivars were chosen: Volodar, Determinant 11, Anita Belorusskaia, Iliia, Charovnitsa, Lakneia, Ufimskaia Primorskaia 7, Batyr, Mordovskaia 124, Ceska Krajova, Ketovace, Arno; by plasticity, Yelena, Podolianka, Roksolana, Populiatsiia 7/07, Olha, CИН 3/02, Sofia, П-330, П-455, П-620, Yaroslavna, Sumchanka, Selianochka, Ruslana, Slobozhanka, Ariesa, and Ceska Krajova were the best; by selection value, Roksolana, Volodar, П-332б П-455, Determinant 11, П-485, Selianochka, Slobozhanka, Anita Belorusskaia, Iliia, Lakneia, Marta, Adigel, Ufimskaia, Batyr, Mordovskaia 124, Ceska Krajova, Ketavace, and Arno were the best varieties.